Two-dimensional nanosheet / filler composite lithium metal negative electrode material as well as preparation method and application thereof

Through the preparation method of two-dimensional nanosheet/filler composite lithium metal negative electrode material, the problems of uneven deposition of lithium metal and easy rupture in lithium-ion batteries are solved, and uniform deposition of lithium ions and efficient and stable cycle of the battery are achieved.

CN120376563APending Publication Date: 2025-07-25CENT SOUTH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510543295.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The theoretical capacity of graphite negative electrodes of existing lithium-ion batteries is low, making it difficult to adapt to the volume effect and current density problems during lithium metal deposition/dissolution, resulting in frequent interface reactions, easy SEI film to break, and deterioration of battery performance.

Method used

The preparation method of two-dimensional nanosheets/filler composite lithium metal negative electrode material is adopted. Through the roll-stack-rolling process, the two-dimensional layered material and filler are uniformly laid on the surface of the lithium metal foil to form a composite structure. The two-dimensional nanosheets are used as surface protective layers to reduce the possibility of side reactions and SEI film rupture, and achieve uniform deposition of lithium ions.

Benefits of technology

Effectively reduce the side reaction between lithium sheets and electrolyte, improve the uniform deposition and stable circulation performance of lithium metal, extend the stable circulation time of the battery, reduce the current density on the electrode surface, and control the volume expansion of lithium metal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120376563A_ABST
    Figure CN120376563A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of battery materials, and discloses a two-dimensional nanosheet / filler composite lithium metal negative electrode material and a preparation method and application thereof.The preparation method comprises the steps that a two-dimensional layered material is evenly laid on the surface of a lithium metal foil, rolling is conducted, and a foil A1 is obtained; the foil A1 is stacked and rolled into sheets again, and a foil A2 is obtained; stacking and rolling are repeated, and a foil An is obtained; uniformly paving a filler on the surface of the foil An, and rolling to obtain a foil B1; the foil B1 is stacked and rolled into sheets again, and foil B2 is obtained; and stacking and rolling are repeated, foil Bn is obtained, and the foil Bn is the two-dimensional nanosheet / filler composite lithium metal negative electrode material. The lithium metal foil is optimized through the two-dimensional layered material and the filler, and the rolling-stacking-rolling process is combined, so that the possibility of side reaction between a lithium sheet and an electrolyte is reduced, the surface current density of the battery is reduced, and the stable cycle time is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of battery materials, and relates to a lithium metal negative electrode material, specifically to a two-dimensional nanosheet / filler composite lithium metal negative electrode material, its preparation method and application. Background Art

[0002] Lithium-ion batteries are widely used in the fields of power batteries and energy storage batteries. However, the theoretical capacity of the graphite negative electrode used in them is relatively low, which limits the development of high specific energy batteries. Therefore, there is an urgent need to develop negative electrode materials with higher specific energy. Lithium metal, with a high theoretical specific capacity (3860 mAh / g), the lowest electrode potential (-3.04 V vs. SHE), and a low density (0.53 g / cm 3 ) is an excellent negative electrode material for lithium batteries.

[0003] Lithium metal foils are often used as lithium metal negative electrodes. By constructing an artificial interface layer (SEI) on the surface of lithium metal, the interfacial reaction and dendrite growth caused by the SEI film generated during the operation of the battery between lithium metal and electrolyte can be effectively alleviated. However, there are two bottleneck problems with planar lithium metal negative electrodes. Firstly, the planar lithium negative electrode structure is difficult to adapt to the volume effect generated during lithium metal deposition / dissolution. The huge volume change brought about by the areal capacity will cause damage to the interfacial layer. Secondly, the relatively small specific surface area will result in an excessive current density on the electrode surface, triggering uneven deposition of lithium metal and making it easier to generate lithium dendrites.

[0004] In the prior art, a three-dimensional lithium metal negative electrode is usually constructed to provide a host space for lithium ion deposition, slowing down the volume effect brought about by lithium ion deposition. At the same time, it has a high specific surface area, which can effectively reduce the surface current density of the electrode and achieve uniform deposition of lithium ions. However, the high specific surface area of the three-dimensional lithium negative electrode will lead to an increase in side reactions between the electrolyte and the lithium metal negative electrode, consuming more electrolyte. Moreover, the SEI film on the surface of the three-dimensional lithium negative electrode is easily broken and regenerated, quickly consuming the active substances in the battery, and ultimately deteriorating the battery performance. In addition, how to avoid the preferential deposition of metallic lithium on the outer surface of the three-dimensional lithium negative electrode facing the membrane, but to uniformly deposit it on the inner surface of the three-dimensional lithium negative electrode, especially to truly achieve low volume strain under high current, is a difficult problem that urgently needs to be solved for the three-dimensional lithium negative electrode. Summary of the Invention

[0005] Aiming at the defects and deficiencies existing in the prior art, on the first aspect, the present invention provides a preparation method for a two-dimensional nanosheet / filler composite lithium metal negative electrode material; on the second aspect, the present invention provides a two-dimensional nanosheet / filler composite lithium metal negative electrode material; on the third aspect, the present invention provides a battery.

[0006] In a first aspect, the present invention provides a method for preparing a two-dimensional nanosheet / filler composite lithium metal anode material, comprising the following steps: Step 1: Uniformly lay a two-dimensional layered material on the surface of a lithium metal foil, and then roll it. After rolling the two-dimensional layered material into the lithium metal foil, foil A1 is obtained; Step 2: Stack foil A1 and roll it into a sheet again to obtain foil A2; Step 3: Repeat Step 2 multiple times to obtain foil A n ; Step 4: Uniformly lay a filler on the surface of foil A n and then roll it. After rolling the filler into foil A n to obtain foil B1; Step 5: Stack foil B1 and roll it into a sheet again to obtain foil B2; Step 6: Repeat Step 5 multiple times to obtain foil B n , and the foil B n is the two-dimensional nanosheet / filler composite lithium metal anode material.

[0007] Preferably, in Step 1, the thickness of the lithium metal foil is 400 - 500 μm.

[0008] Preferably, in Step 1, the two-dimensional layered material is any one or more of graphite materials, boron nitride, molybdenum disulfide, tungsten disulfide, molybdenum diselenide, tungsten diselenide, montmorillonite, kaolin, vermiculite, MXene materials, etc.

[0009] Preferably, in Step 1, the mass ratio of the two-dimensional layered material to the lithium metal foil is 1:5 - 50; more preferably, the mass ratio of the two-dimensional layered material to the lithium metal foil is 1:8 - 22; even more preferably, the mass ratio of the two-dimensional layered material to the lithium metal foil is 1:9 - 12.

[0010] Preferably, in Step 1, the thickness of foil A1 is 50 - 100 μm.

[0011] Preferably, in Step 2, the number of layers of stacked foil A1 is 3 - 6 layers; the total thickness after stacking multiple layers of foil A1 is 150 - 400 μm.

[0012] Preferably, in Step 3, the number of times of repeating Step 2 is 5 - 60 times, more preferably, the number of times of repeating Step 2 is 15 - 30 times.

[0013] Preferably, in Step 4, the filler is one or more of metal materials, inorganic non-metallic materials, organic materials, and composites of the above materials, etc.

[0014] Preferably, the metal material is any one or more than two of pure metals and alloys; more preferably, the metal material is any one of Ag, Zn, Sn and its alloys or more than two of them.

[0015] Preferably, the inorganic non-metallic material is any one or more than two of oxides, sulfides, carbides, nitrides, fluorides, phosphides, selenides, bromides, iodides.

[0016] Preferably, the oxide is any one or more than two of Al2O3, ZnO, MgO; the sulfide is any one or more than two of ZnS, FeS, SnS2; the carbide is any one or more than two of TiC, SiC, B4C; the nitride is any one or more than two of TiN, Zn3N2, Si3N4; the fluoride is any one or more than two of MgF2, SnF2, ZnF; the phosphide is any one or more than two of Ni2P, Cu3P, FeP; the selenide is any one or more than two of SnSe, ZnSe, MgSe; the bromide is any one or more than two of MgBr2, NaBr, KBr; the iodide is any one or more than two of ZnI2, CsI, KI.

[0017] Preferably, in step 4, the mass ratio of the filler to the foil A n is 1:5 to 50; more preferably, the mass ratio of the filler to the foil A n is 1:8 to 22; even more preferably, the mass ratio of the filler to the foil A n is 1:9 to 12.

[0018] Preferably, in step 5, the number of layers of the stacked foil B1 is 3 to 6 layers; the total thickness of the stacked multi-layer foil B1 is 150 to 400 μm.

[0019] Preferably, in step 6, the number of times of repeating step 5 is 5 to 100 times, more preferably, the number of times of repeating step 5 is 10 to 30 times.

[0020] Preferably, it further includes: performing surface delithiation treatment on the two-dimensional nanosheet / filler composite lithium metal negative electrode material.

[0021] Preferably, the process of the surface delithiation treatment is: using an electrochemical method to remove the lithium metal on the surface of the two-dimensional nanosheet / filler composite lithium metal foil, so that the two-dimensional nanosheets and the filler are exposed on the surface of the two-dimensional nanosheet / filler composite lithium metal negative electrode material.

[0022] Preferably, the surface delithiation amount is 1 to 10 mAh / cm 2 .

[0023] In a second aspect, the present invention provides a two-dimensional nanosheet / filler composite lithium metal negative electrode material prepared by the above preparation method.

[0024] In a third aspect, the present invention provides a battery comprising the two-dimensional nanosheet / filler composite lithium metal negative electrode material prepared by the above preparation method.

[0025] Compared with the prior art, the present invention has the following obvious beneficial effects: Through the preparation method provided by the present invention, in the first aspect, through the repeated process of rolling - stacking - rolling, the two-dimensional layered material is peeled inside the lithium metal, and the two-dimensional layered material is gradually peeled into few-layer two-dimensional nanosheets. After surface delithiation treatment, the two-dimensional nanosheets are stacked on the surface of the lithium metal as a surface protection layer, which can reduce the possibility of side reactions between the lithium sheet and the electrolyte; in the second aspect, the stretchable property of the two-dimensional nanosheets conforms to the internal three-dimensional lithium metal, and the protection of the two-dimensional nanosheet stacking film can reduce the possibility of SEI film fragmentation and reduce the electrolyte loss during the fragmentation - regeneration process of the SEI film; in the third aspect, since the overpotential of lithium ions deposited on the surface of the two-dimensional nanosheets is greater than that directly deposited on the surface of the lithium metal, lithium ions are preferentially deposited on the three-dimensional structure inside the lithium negative electrode, which can effectively reduce the surface current density of the electrode, achieve uniform deposition of lithium metal and control the volume expansion of lithium metal. Description of the Drawings

[0026] Figure 1 It is a battery test performance diagram after assembling the delithiated two-dimensional nanosheet / filler composite lithium metal negative electrode material prepared in Example 1 into a symmetric battery. Detailed Embodiments

[0027] The present invention provides the following specific technical solutions.

[0028] In a first aspect, the present invention provides a preparation method of a two-dimensional nanosheet / filler composite lithium metal negative electrode material, comprising the following steps: Step 1, uniformly lay the two-dimensional layered material on the surface of the lithium metal foil and then roll it. After rolling the two-dimensional layered material into the lithium metal foil, foil A1 is obtained; Step 2, stack foil A1 and roll it into a sheet again to obtain foil A2; Step 3, repeat Step 2 multiple times to obtain foil A n ; Step 4, uniformly lay the filler on the surface of foil A n and then roll it. Roll the filler into foil An After that, the foil material B1 is obtained; Step 5: Stack the foil material B1 and roll it into a sheet again to obtain the foil material B2; Step 6: Repeat Step 5 multiple times to obtain the foil material B n , and the foil material B n is the two-dimensional nanosheet / filler composite lithium metal anode material.

[0029] The inventor has found through research that in the two-dimensional nanosheet / filler composite lithium metal anode material prepared by the preparation method provided by the present invention, metallic lithium is used as the matrix material and the main framework of the anode material. During the preparation process, it still maintains a relatively continuous structure after multiple operations such as rolling, and runs through the entire anode material; during the repeated rolling process of the two-dimensional layered material, the two-dimensional layered material is peeled into few-layer two-dimensional nanosheets. The two-dimensional nanosheets are distributed in a layered manner inside the lithium metal foil. Moreover, as the number of repeated operations increases, the dispersion degree of the two-dimensional nanosheets is higher and the distribution is more uniform. They can be tightly combined with the lithium metal foil and become a reinforcing phase inside the lithium metal foil; during the stacking and rolling process, the filler is evenly distributed inside the foil material, embedded in the lithium metal, and intertwined with the two-dimensional nanosheets to form a complex three-dimensional distribution structure, making the structure of the entire composite anode material denser and more stable. The prepared anode material macroscopically presents a three-dimensional structure in which two-dimensional nanosheets (two-dimensional layered materials), fillers, and lithium metal are mutually composite.

[0030] In the first aspect, through the repeated process of rolling-stacking-rolling, the two-dimensional layered material is peeled inside the lithium metal, and the two-dimensional layered material is gradually peeled into few-layer two-dimensional nanosheets. After surface delithiation treatment, the two-dimensional nanosheets are stacked on the surface of the lithium metal as a surface protection layer, which can reduce the possibility of side reactions between the lithium sheet and the electrolyte; in the second aspect, the stretchable characteristics of the two-dimensional nanosheets are conformal with the internal three-dimensional lithium metal. The protection of the two-dimensional nanosheet stacking film can reduce the possibility of the SEI film breaking and reduce the electrolyte loss during the breaking-regeneration process of the SEI film; in the third aspect, since the overpotential for lithium ions to deposit on the surface of the two-dimensional nanosheets is greater than that for directly depositing on the surface of the lithium metal, lithium ions preferentially deposit on the three-dimensional structure inside the lithium negative electrode, which can effectively reduce the surface current density of the electrode, achieve uniform deposition of lithium metal, and control the volume expansion of lithium metal; in the fourth aspect, the composite lithium metal anode with a two-dimensional nanosheet / filler framework can effectively improve the ion transport rate inside the lithium metal anode and uniform the current, effectively prevent the growth of lithium dendrites and reduce volume changes, so as to achieve stable cycling at high current density and high capacity.

[0031] Preferably, in Step 1, the thickness of the lithium metal foil is 400-500 μm.

[0032] Preferably, in step 1, the two-dimensional layered material is any one or more of graphite materials, boron nitride, molybdenum disulfide, tungsten disulfide, molybdenum diselenide, tungsten diselenide, montmorillonite, kaolin, vermiculite, MXene materials.

[0033] The inventors have found through research that two-dimensional layered materials have a large specific surface area, can provide more active sites to interact with lithium ions, are beneficial to the adsorption and transmission of lithium ions, thereby improving the charge-discharge efficiency and rate performance of the battery. After the two-dimensional layered material is compounded with lithium metal, the formed special interlayer structure can accommodate lithium ions, play a role in buffering and storing lithium ions, and at the same time can also regulate the transmission path of lithium ions, making the distribution of lithium ions more uniform, thereby inhibiting the growth of lithium dendrites.

[0034] Preferably, in step 1, the mass ratio of the two-dimensional layered material to the lithium metal foil is 1:5 to 50; more preferably, the mass ratio of the two-dimensional layered material to the lithium metal foil is 1:8 to 22; even more preferably, the mass ratio of the two-dimensional layered material to the lithium metal foil is 1:9 to 12.

[0035] The inventors have found through research that when the mass ratio of the two-dimensional layered material to the lithium metal foil is controlled within a reasonable range, the interaction between the two-dimensional layered material and the lithium metal reaches an ideal state, and the advantages of the two-dimensional layered material can be maximally exerted, such as fully inhibiting the growth of lithium dendrites, significantly improving the cycle life and rate performance of the battery, etc. While ensuring the material performance, avoid using too much expensive two-dimensional layered material, thereby reducing the production cost and improving the economy of material preparation. If the amount of the two-dimensional layered material used is too much, it will not only increase the cost, but may also have adverse effects such as agglomeration due to excess, which will instead reduce the material performance.

[0036] Preferably, in step 1, the thickness of the foil A1 is 50 to 100 μm.

[0037] Preferably, in step 2, the number of layers of the stacked foil A1 is 3 to 6 layers; the total thickness of the stacked multi-layer foil A1 is 150 to 400 μm.

[0038] Preferably, in step 3, the number of times of repeating step 2 is 5 to 100 times, more preferably, the number of times of repeating step 2 is 10 to 30 times.

[0039] Preferably, in step 4, the filler is one or more of metal materials, inorganic non-metallic materials, organic materials, and composites of the above materials, etc.

[0040] The inventors have found through research that when the filler is selected as a metal material and added to the lithium metal negative electrode, it can improve the ion / electron transport efficiency of the electrode, reduce the internal resistance of the battery, thereby improving the charge-discharge performance and rate performance of the battery.

[0041] The filler is selected from inorganic non-metallic materials, which have special crystal structures and ionic conduction characteristics. They can provide fast-transmission channels for lithium ions, promote the uniform distribution of lithium ions in the electrode, inhibit the growth of lithium dendrites, and improve the cycling performance and stability of the battery.

[0042] The filler is selected from organic materials, which can form a uniform protective film on the surface of the lithium metal, improve the interfacial compatibility between the electrode and the electrolyte, reduce the interfacial resistance, inhibit the occurrence of side reactions, and thus improve the performance and safety of the battery.

[0043] Preferably, the metal material is any one or two or more of pure metals and alloys; more preferably, the metal material is any one of Ag, Zn, Sn and its alloys or two or more.

[0044] Preferably, the inorganic non-metallic material is any one or two or more of oxides, sulfides, carbides, nitrides, fluorides, phosphides, selenides, bromides, iodides.

[0045] More preferably, the oxide is any one or two or more of Al2O3, ZnO, MgO; The sulfide is any one or two or more of ZnS, FeS, SnS2; The carbide is any one or two or more of TiC, SiC, B4C; The nitride is any one or two or more of TiN, Zn3N2, Si3N4; The fluoride is any one or two or more of MgF2, SnF2, ZnF; The phosphide is any one or two or more of Ni2P, Cu3P, FeP; The selenide is any one or two or more of SnSe, ZnSe, MgSe; The bromide is any one or two or more of MgBr2, NaBr, KBr; The iodide is any one or two or more of ZnI2, CsI, KI.

[0046] Preferably, in step 4, the mass ratio of the filler to foil A n is 1:5 to 50; more preferably, the mass ratio of the filler to foil A n is 1:8 to 22; even more preferably, the mass ratio of the filler to foil A n is 1:9 to 12.

[0047] Preferably, in step 5, the number of layers of stacked foil B1 is 3 to 6 layers; the total thickness of the stacked multi-layer foil B1 is 150 to 400 μm.

[0048] Preferably, in step 6, the number of times of repeating step 5 is 5 to 100 times, and further preferably, the number of times of repeating step 5 is 15 to 30 times.

[0049] Preferably, it further includes: performing surface delithiation treatment on the two-dimensional nanosheet / filler composite lithium metal anode material.

[0050] Preferably, the process of the surface delithiation treatment is: using an electrochemical method to remove lithium metal from the surface of the two-dimensional nanosheet / filler composite lithium metal foil, so that the two-dimensional nanosheets and fillers are exposed on the surface of the two-dimensional nanosheet / filler composite lithium metal anode material.

[0051] Preferably, the surface delithiation amount is 1 to 20 mAh / cm 2 .

[0052] In a second aspect, the present invention provides a two-dimensional nanosheet / filler composite lithium metal anode material prepared by the above preparation method.

[0053] In a third aspect, the present invention provides a battery, including the two-dimensional nanosheet / filler composite lithium metal anode material prepared by the above preparation method or the above two-dimensional nanosheet / filler composite lithium metal anode material.

[0054] To make the technical problems, technical solutions and technical advantages to be solved by the present invention clearer, the following will be described in detail with specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0055] Unless otherwise defined, all professional terms used hereinafter have the same meaning as commonly understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the protection scope of the present invention.

[0056] Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be obtained through market purchase or can be prepared by existing methods.

[0057] Example 1: A preparation method of a two-dimensional nanosheet / filler composite lithium metal anode material includes the following steps: Step 1, uniformly lay natural flake graphite on the surface of a lithium metal foil with a thickness of 400 μm. The mass ratio of natural flake graphite to the lithium metal foil is 1:10. Roll the natural flake graphite into the lithium metal foil, and then continue to roll until the thickness of the lithium metal foil is 50 μm to obtain foil A1.

[0058] Step 2, fold the foil A1 obtained in step 1 twice (or stack four layers of foil A1), and then roll it into a sheet again to obtain foil A2 with a thickness of 50 μm.

[0059] Step 3: Repeat Steps 1 - 2 twenty - nine times to obtain Foil A. 30 . During the process of repeating the steps, natural flake graphite is gradually exfoliated into few - layer two - dimensional graphene nanosheets, i.e., two - dimensional nanosheets.

[0060] Step 4: Uniformly lay zinc metal nanoparticles on the surface of Foil A. 30 The mass ratio of zinc metal nanoparticles to Foil A is 1:10. Roll the zinc metal nanoparticles into Foil A to obtain Foil B1. 30 30

[0061] Step 5: Fold the Foil B1 prepared in Step 4 twice (or stack four layers of Foil B1), and then roll it into a sheet again to obtain Foil B2 with a thickness of 50 μm.

[0062] Step 6: Repeat Steps 4 - 5 twenty - nine times to obtain Foil B 30 , which is the two - dimensional nanosheet / filler composite lithium metal anode material.

[0063] Step 7: Place the two - dimensional nanosheet / filler composite lithium metal anode material prepared in Step 6 under a current density of 1 mA / cm 2 for delithiation treatment, and extract 5 mAh / cm 2 of lithium capacity, removing part of the lithium metal on the surface of Foil B 30 so that the natural flake graphite and zinc metal nanoparticles on the surface are exposed, i.e., the delithiation is completed.

[0064] Battery test: Assemble symmetric batteries with the delithiated two - dimensional nanosheet / filler composite lithium metal anode material prepared in Step 7 as the working electrode and the counter electrode respectively. The electrolyte is 1 M LiTFSI in DOL∶DME = 1∶1 Vol%, and assemble CR2025 coin cells in a glove box filled with argon atmosphere. When performing battery charge - discharge tests, the current density is 3 mA / cm 2 , and the areal specific capacity is 3 mAh / cm 2 .

[0065] Figure 1 is the battery test performance graph of the symmetric battery assembled with the delithiated two - dimensional nanosheet / filler composite lithium metal anode material prepared in Example 1. Figure 1It can be seen that the overpotential of the symmetrical battery is 36mV, which proves that the reaction rate of the electrode surface of the two-dimensional nanosheet / filler composite lithium metal negative electrode material is fast during the charge and discharge process, and the ion transmission and electron conduction performance are good, without obvious obstruction or retardation, so that the battery can be charged and discharged with a small voltage loss; it can be proved from the side that lithium ions preferentially deposit metal in the three-dimensional structure inside the lithium negative electrode, effectively reducing the surface current density of the electrode, achieving uniform deposition of lithium metal and controlling the volume expansion of lithium metal. The stable cycle time is 2200h, which proves that the structure of the electrode material is stable and the durability and reversibility of the battery are good. It can be proved from the side that the possibility of side reactions between the electrode sheet and the electrolyte is reduced, and the electrolyte loss due to the breakage-regeneration process of the SEI film is reduced.

[0066] The difference between Examples 2 to 4 and Example 1 is that the two-dimensional layered materials used in step 1 are different. The test results of the batteries assembled with the two-dimensional layered materials used in Examples 2 to 4 and the prepared negative electrode materials are shown in Table 1. The assembly and testing process of the batteries is the same as that of Example 1.

[0067] Table 1 Two-dimensional layered materials used in Examples 2 to 4 and test results By comparing the test results of the batteries assembled with the negative electrode materials prepared in Example 1 and Example 2, it can be seen that the battery assembled with the negative electrode materials prepared in Example 2 has a higher overpotential and a shorter stable cycle time. The inventor speculates that the reason for this phenomenon may be: the crystal development of natural flake graphite is relatively complete, the friction coefficient is small, the lubricity is best, and the plasticity is highest, while dense crystalline graphite and cryptocrystalline graphite are second, and artificial layered graphite is relatively poor, with a larger friction coefficient and worse lubricity. Therefore, it is more difficult to peel into uniform and thin graphene nanosheets during the rolling process, and it is difficult to effectively form a perfect graphene SEI film that can conformally deform with lithium metal, so that the side reactions between the electrolyte and lithium metal are more than the SEI film formed using natural graphite, resulting in worse performance, increased overpotential, and reduced stable cycle time.

[0068] Comparing the test results of the batteries assembled with the negative electrode materials prepared in Comparative Example 1 and Example 3, the battery assembled with the negative electrode material prepared in Example 3 has a higher overpotential and a shorter stable cycling duration. The inventor speculates that the reason for this phenomenon may be that lithiated montmorillonite has good exfoliation properties and can be exfoliated into few-layer structures during the rolling process, forming a better artificial SEI film after pre-lithiation. However, the number, distribution, and activity of the surface active sites of lithiated montmorillonite may be different from those of two-dimensional graphene, which will affect the reaction kinetics of lithium ions on the electrode surface, slow down the reaction rate, and increase the overpotential. Moreover, after delithiation treatment, the two-dimensional structure on the surface of two-dimensional graphene can be better exposed, and the chemical reactions with the electrolyte and lithium metal are relatively stable and reversible. After delithiation, the lithiated montmorillonite structure on the surface of lithiated montmorillonite may undergo some irreversible changes, resulting in a decrease in the reversibility of the surface chemical reaction, thus affecting the cycling performance of the battery and shortening the stable cycling duration.

[0069] Comparing the test results of the batteries assembled with the negative electrode materials prepared in Comparative Example 1 and Example 4, the battery assembled with the negative electrode material prepared in Example 4 has a higher overpotential and a shorter stable cycling duration. The inventor speculates that the reason for this phenomenon may be that MoS2 is more difficult to exfoliate, so a thicker artificial SEI film is formed, resulting in poor ion transport, thus increasing the overpotential and decreasing the cycling duration.

[0070] The differences between Examples 5-6 and Example 1 are as follows: in Step 1, the mass ratio of the two-dimensional layered material to the lithium metal foil is different. The mass ratio of the two-dimensional layered material to the lithium metal foil in Examples 5-6 and the test results of the batteries assembled with the prepared negative electrode materials are shown in Table 2: Table 2 Mass ratio of two-dimensional layered material to lithium metal foil and test results in Examples 5-6 Comparing the test results of the batteries assembled with the negative electrode materials prepared in Comparative Example 1 and Example 5, the battery assembled with the negative electrode material prepared in Example 5 has a higher overpotential and a shorter stable cycling duration. The inventor speculates that the reason for this phenomenon may be that in Example 5, the amount of the two-dimensional layered material is relatively small, which will result in an overly thin stacked film layer and cannot effectively protect the internal lithium metal completely. Moreover, the amount of the two-dimensional layered material inside the lithium metal negative electrode is small, reducing the internal ion / electron transport rate.

[0071] Comparing the test results of the batteries assembled with the negative electrode materials prepared in Comparative Example 1 and Example 6, the battery assembled with the negative electrode material prepared in Example 6 has a higher overpotential and a shorter stable cycling duration. The inventor speculates that the reason for this phenomenon may be that: with the increase in the content of the two-dimensional layered material, the thickness of the few-layer two-dimensional nanosheet stacking film on the surface after pre-delithiation will increase, thereby reducing the lithium ion transport efficiency, resulting in an increase in the overpotential. Moreover, there is a risk of lithium metal deposition on the surface of the stacking film, leading to an increase in the side reactions between the lithium metal and the electrolyte, and thus reducing the stable cycling duration.

[0072] The differences between Examples 7 to 10 and Example 1 are as follows: the number of repetitions of Steps 1 to 2 in Step 3. The number of repetitions of Steps 7 to 10 in Step 3 in Examples 7 to 10 and the test results of the batteries assembled with the prepared negative electrode materials are shown in Table 3.

[0073] Table 3 The number of repetitions of Steps 1 to 2 in Step 3 in Examples 7 to 10 and the test results Combining the test results of the batteries assembled with the negative electrode materials prepared in Examples 7 to 10, the inventor speculates that: if the number of rolling presses is too small, the two-dimensional layered material cannot be effectively peeled into thin two-dimensional nanosheets, so a composite structure and a surface stacking film cannot be effectively formed; if the number of rolling presses is too large, special crystal plane orientations will appear unevenly in the metallic lithium, resulting in selective sites for deposition and stripping during the deposition and stripping of lithium metal, leading to an inhomogeneous interface, thus affecting the overpotential and stable cycling duration of the battery.

[0074] The differences between Examples 11 to 16 and Example 1 are as follows: the different fillers used in Step 4. The fillers used in Examples 11 to 16 and the test results of the batteries assembled with the prepared negative electrode materials are shown in Table 4.

[0075] Table 4 The two-dimensional layered materials used in Examples 11 to 16 and the test results Combining the test results of the batteries assembled with the negative electrode materials prepared in Examples 11 to 16, the inventor proposes that: when the filler is a metal material, the lithiophilicity of the metal material has a great influence on the performance of the finally prepared negative electrode material. The lithiophilicity of nano nickel powder, nano cobalt powder, nano cobalt powder and nano tin powder increases in turn. Therefore, the overpotentials of the batteries assembled with the negative electrode materials prepared in Examples 11 to 14 decrease in turn, and the stable cycling durations increase in turn.

[0076] Based on the test results of the battery assembled with the negative electrode material prepared in Example 15, the inventor speculates that: after lithiation, nano-SiO₂ forms a lithium-silicon alloy, which is prone to excessive volume expansion and leads to silicon powdering, thus resulting in an increase in the overpotential and a decrease in the stable cycling duration.

[0077] Based on the test results of the battery assembled with the negative electrode material prepared according to Example 16, the inventors speculated that: alumina is compounded with lithium flakes as a filler. During the operation of the battery, part of the lithium element in the lithium flakes is converted into lithium oxide. The formation of lithium oxide can change the properties of the electrode surface to a certain extent, making the nucleation of lithium on the electrode surface easier; and lithium oxide has high ionic conductivity, which can promote the migration and diffusion of lithium ions, provide more active sites for the deposition of lithium, and thus reduce the overpotential during lithium deposition; alumina as a filler has high stability and certain ionic conduction ability. Acting together with lithium oxide, it helps to maintain the stability of the electrode structure, reduce the polarization phenomenon of the electrode during charge and discharge. The reduction of the polarization degree means that the energy loss of the battery during charge and discharge is reduced, and the overpotential will also be reduced accordingly, thereby improving the charge and discharge efficiency of the battery.

[0078] The differences between Examples 17 to 18 and Example 1 are as follows: in Step 4, the mass ratio of the filler to the foil An is different. The mass ratio of the filler to the foil An in Examples 17 to 18 and the test results of the batteries assembled with the prepared negative electrode materials are shown in Table 5.

[0079] Table 5 Mass ratio of the filler to the foil An in Examples 17 to 18 and test results Based on the test results of the batteries assembled with the negative electrode materials prepared in combination with Examples 1, 17, and 18, the inventors speculated that: when the filler is less, it cannot effectively improve the ionic / electronic conductivity inside the lithium metal negative electrode and support the three-dimensional structure; when the filler is more, the filler appears as a non-uniform local negative electrode, that is, it causes the preferential deposition of lithium ions in local areas and also hinders the deposition and stripping channels of lithium metal, thus affecting the electrochemical performance of the battery.

[0080] The differences between Examples 19 to 22 and Example 1 are as follows: in Step 5, the number of times of repeating Steps 4 to 5 is different. The number of times of repeating Steps 4 to 5 in Examples 19 to 22 and the test results of the batteries assembled with the prepared negative electrode materials are shown in Table 6.

[0081] Table 6 Number of times of repeating Steps 4 to 5 in Examples 19 to 22 and test results Based on the test results of the batteries assembled with the negative electrode materials prepared in combination with Examples 1, 19, and 20, the inventors speculated that: if the number of times of repeating Steps 4 to 5 in Step 5 is too small, the filler cannot be effectively dispersed, resulting in non-uniformity of the filler inside the lithium metal; if the number of times of repeating Steps 4 to 5 in Step 5 is too large, it may damage the composite structure of the internal two-dimensional nanosheets and the filler; both affect the structural stability of the negative electrode material, thereby affecting the electrochemical performance of the battery.

[0082] Comparative Example 1: A method for preparing a negative electrode material, comprising the following steps: Step 1: Fold a lithium metal foil twice (or stack four layers of lithium metal foils), roll it into a sheet to obtain Foil A1, and the thickness of Foil A1 is 50 μm.

[0083] Step 2: Repeat Step 1 a total of 49 times to obtain Foil A 50 .

[0084] Comparative Example 2: A method for preparing a two-dimensional nanosheet composite lithium metal negative electrode material, comprising the following steps: Step 1: Uniformly lay natural flake graphite on the surface of a lithium metal foil with a thickness of 400 μm. The mass ratio of natural flake graphite to the lithium metal foil is 1:10. Roll the natural flake graphite into the lithium metal foil, and then continue to roll until the thickness of the lithium metal foil is 50 μm to obtain Foil A1.

[0085] Step 2: Fold the Foil A1 obtained in Step 1 twice (or stack four layers of Foil A1), and then roll it into a sheet again to obtain Foil A2, and the thickness of Foil A2 is 50 μm.

[0086] Step 3: Repeat Steps 1 to 2 a total of 29 times to obtain the foil. During the repeated steps, the natural flake graphite is gradually exfoliated into few-layer two-dimensional graphene nanosheets, i.e., two-dimensional nanosheets.

[0087] Step 4: Place the foil obtained in Step 3 under a current density of 1 mA / cm 2 for delithiation treatment, and extract 5 mAh / cm 2 of lithium capacity to remove part of the lithium metal on the surface of the foil, so that the two-dimensional graphene on the surface is exposed, i.e., the delithiation is completed, and it is the composite lithium metal negative electrode material.

[0088] Comparative Example 3: A method for preparing a filler composite lithium metal negative electrode material, comprising the following steps: Step 1: Uniformly lay zinc metal nanoparticles on the surface of a lithium metal foil with a thickness of 400 μm. The mass ratio of zinc metal nanoparticles to the lithium metal foil is 1:10. Roll the zinc metal nanoparticles into the lithium metal foil, and then continue to roll until the thickness of the lithium metal foil is 50 μm to obtain Foil A1.

[0089] Step 2: Fold the Foil A1 obtained in Step 1 twice (or stack four layers of Foil A1), and then roll it into a sheet again to obtain Foil A2, and the thickness of Foil A2 is 50 μm.

[0090] Step 3: Repeat Steps 1 - 2 for 29 times, and the obtained foil is the filler - composite lithium metal anode material.

[0091] The lithium metal anode materials prepared in Comparative Examples 1 - 3 were used as the working electrode and the counter electrode to assemble symmetric cells respectively. The electrolyte was 1M LiTFSI / DOL∶DME Vol%, and CR2025 coin cells were assembled in a glove box filled with an argon atmosphere. When testing the charge - discharge of the cells, the current density was 3 mA / cm 2 , and the areal specific capacity was 3 mAh / cm 2 ; The test results are shown in Table 7.

[0092] Table 7 Test results of the cells assembled with the lithium metal anode materials prepared in Comparative Examples 1 - 3 Comparative Example 1 is the anode material without treatment with two - dimensional layered materials and fillers.

[0093] Comparative Example 2 is the anode material treated only with two - dimensional layered materials. Its over - potential is relatively low, but the stable cycling duration is short. The inventor speculates that it may be: when only two - dimensional layered materials are contained, at 3 mAh / cm 2 condition, that is, under a relatively large lithium deposition / stripping capacity, due to the lack of filler support, the structure of the lithium metal anode is prone to collapse. That is, during the lithium metal deposition and stripping process, the two - dimensional layered materials are prone to gradually stack, resulting in a relatively thick surface artificial SEI film, and then rapid attenuation. Therefore, although its over - potential is low, it only exists in the initial cycling stage. In the subsequent cycling process, as the anode structure changes, the over - potential will gradually increase until it fails.

[0094] Comparative Example 3 is the anode material treated only with fillers. Its over - potential is relatively low, and the stable cycling duration is short. The inventor speculates that it may be: when the filler is directly combined with the lithium metal foil, due to the lack of an intermediate transition layer, the bonding force between the two may be weak. During the subsequent charge - discharge process of the cell, the electrode material will experience volume changes, and insufficient bonding force may lead to separation, shedding, etc. between the filler and the lithium metal foil, affecting the over - potential and stable cycling duration of the cell. Moreover, during the process of evenly laying the filler on the surface of the lithium metal foil and rolling it in, compared with the method of first using two - dimensional layered materials and then introducing fillers, when only fillers are used, it is more difficult to control the uniformity of the filler on the foil surface. Uneven filler distribution will lead to inconsistent electrochemical activity on the electrode surface, prone to uneven local current density during the charge - discharge process, and then trigger uneven growth of lithium dendrites, increasing the risk of battery short - circuit and reducing the cycling performance and safety of the battery.

[0095] Comparing the test results of the batteries assembled with the lithium metal anode materials prepared in Example 1 and Comparative Examples 1 to 3 respectively can further prove that the anode material prepared by the preparation method provided by the present invention has good ion / electron transport efficiency and cycle stability, achieving the effect of 1 + 1 > 2.

[0096] The above-described embodiments are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope of the present invention, according to the technical solution and its concept of the present invention, making equivalent substitutions or changes should be covered within the protection scope of the present invention.

Claims

1. A preparation method of a two-dimensional nanosheet / filler composite lithium metal anode material, characterized in that, It includes the following steps: Step 1: Uniformly lay a two-dimensional layered material on the surface of a lithium metal foil, and then perform rolling. After rolling the two-dimensional layered material into the lithium metal foil, foil A1 is obtained. Step 2: Stack foil A1 and roll it into a sheet again to obtain foil A2. Step 3, repeat Step 2 multiple times to obtain foil A n ; Step 4, evenly lay the filler on the surface of Foil A n and then perform rolling so that the filler is rolled and embedded into Foil A n to obtain Foil B1 after embedding; Step 5: Stack foil B1 and roll it into a sheet again to obtain foil B2. Step 6. Repeat Step 5 multiple times to obtain foil B n , and the foil B n is the two-dimensional nanosheet / filler composite lithium metal anode material 2. The preparation method of the two-dimensional nanosheet / filler composite lithium metal anode material according to claim 1, characterized in that, In Step 1, the two-dimensional layered material is any one or more than two of graphite materials, boron nitride, molybdenum disulfide, tungsten disulfide, molybdenum diselenide, tungsten diselenide, montmorillonite, kaolin, vermiculite, MXene materials; the mass ratio of the two-dimensional layered material to the lithium metal foil is 1:5 - 50.

3. The preparation method of the two-dimensional nanosheet / filler composite lithium metal anode material according to claim 1, wherein, In Step 2, the number of layers of stacked foil A1 is 3 - 6 layers; the total thickness after stacking multiple layers of foil A1 is 150 - 400 μm; in Step 3, the number of times of repeating Step 2 is 5 - 60 times.

4. The preparation method of the two-dimensional nanosheet / filler composite lithium metal anode material according to claim 1, characterized in that, In Step 4, the filler is one or more of metal materials, inorganic non-metallic materials, organic materials, and composite materials of the above materials, etc. The metal material is any one or more than two of pure metals and alloys. The metal material is any one of Ag, Zn, Sn and its alloy or more than two. The inorganic non-metallic material is any one or more than two of oxides, sulfides, carbides, nitrides, fluorides, phosphides, selenides, bromides, iodides. The oxide is any one or more than two of Al2O3, ZnO, MgO. The sulfide is any one or more than two of ZnS, FeS, SnS2. The carbide is any one or more than two of TiC, SiC, B4C. The nitride is any one or more than two of TiN, Zn3N2, Si3N4. The fluoride is any one or more than two of MgF2, SnF2, ZnF. The phosphide is any one or more than two of Ni2P, Cu3P, FeP. The selenide is any one or more than two of SnSe, ZnSe, MgSe. The bromide is any one or more than two of MgBr2, NaBr, KBr. The iodide is any one or more than two of ZnI2, CsI, KI.

5. The preparation method of the two-dimensional nanosheet / filler composite lithium metal anode material according to claim 1, characterized in that In Step 4, the mass ratio of the filler and Foil A n is 1:5 to 50.

6. The preparation method of the two-dimensional nanosheet / filler composite lithium metal anode material according to claim 1, characterized in that, In Step 5, the number of layers of stacked foil B1 is 3 - 6 layers; the total thickness after stacking multiple layers of foil B1 is 150 - 400 μm; in Step 6, the number of times of repeating Step 5 is 5 - 100 times.

7. The preparation method of the two-dimensional nanosheet / filler composite lithium metal anode material according to claim 1, characterized in that, It also includes: Performing surface delithiation treatment on the two-dimensional nanosheet / filler composite lithium metal anode material.

8. The two-dimensional nanosheet / filler composite lithium metal anode material according to claim 7, wherein The process of surface delithiation is as follows: Electrochemical methods are used to remove the lithium metal on the surface of the two-dimensional nanosheet / filler composite lithium metal foil, so that the two-dimensional nanosheets and fillers are exposed on the surface of the two-dimensional nanosheet / filler composite lithium metal negative electrode material; the surface delithiation amount is 1-10 mAh / cm 2 .

9. A two-dimensional nanosheet / filler composite lithium metal anode material, characterized in that, It is prepared by the preparation method described in any one of claims 1 - 8.

10. A battery, characterized in that, It includes the two-dimensional nanosheet / filler composite lithium metal anode material prepared by the preparation method described in any one of the above claims 1 - 8.

Citation Information

Cited By

  • An ultrathin lithium negative electrode with body phase ion channels and a preparation method and application thereof

    CN122455669A